Distance of the Posterior Interosseous Nerve from the Radial Head during Elbow Arthroscopy: An Anatomical Study - Arrigoni, Paolo; Cucchi, Davide; Guerra, Enrico; Marinelli, Alessandro; Menon, Alessandra; Randelli, Pietro Simone; Pederzini, Luigi Adriano; SIGASCOT Upper Limb Committee (Joints, 2017)
Purpose The aims of this study were to measure the distance of the posterior interosseous nerve (PIN) from the radial head (RH) and its variations with forearm movements.Methods Five fresh frozen cadaver specimens were dissected under arthroscopy. An anterior capsulectomy extended to the entire lateral compartment was performed. The need of soft tissue dissection to isolate the nerve in the extracapsular space was recorded. The distance between the nerve and the anterior part of the RH was then measured with a graduated caliper inserted via the midlateral portal with the forearm in neutral position, full pronation, and full supination.Results The PIN was identifiable in all the specimens. In four cases, it was surrounded by a thick layer of adipose tissue, and further dissection was necessary to isolate it. Damage of the PIN during dissection occurred in one case, in which the proximal part of the nerve was accidentally cut. In three of the remaining cases, an increased distance was measured with the forearm in supination, as compared with neutral and full pronation position.Conclusion This anatomical study suggests that in most of the cases, the PIN does not lay just extracapular at the level of the radiocapitellar joint, but is surrounded by a thick layer of adipose tissue. Furthermore, its distance from the RH appears to increase with forearm supination. This position could increase the safe working space between RH and PIN.Clinical Relevance Knowledge of PIN position in relation to the anterior elbow capsule and its changes with forearm movements can help reduce the iatrogenic injuries during elbow arthroscopy.
Keywords: elbow arthroscopy; posterior interosseous nerve; nerve injury; cadaver